2000
DOI: 10.1152/ajpheart.2000.278.2.h643
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1-derived bilirubin ameliorates postischemic myocardial dysfunction

Abstract: Bilirubin is a potent antioxidant generated intracellularly during the degradation of heme by the enzyme heme oxygenase. The purpose of this study was to determine the role of increased cardiac bilirubin in protection against postischemic myocardial dysfunction. Rat hearts were isolated and perfused according to the Langendorff technique to evaluate the recovery of myocardial function after 30 min of global ischemia and 60 min of reperfusion. We found that upregulation of the inducible isoform of heme oxygenas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
249
1
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 341 publications
(264 citation statements)
references
References 36 publications
12
249
1
2
Order By: Relevance
“…The cytoprotective properties of HO-1 have traditionally been attributed to the by-products of heme degradation, namely bilirubin and carbon monoxide (CO). Indeed, within a narrow therapeutic range, these catalytic by-products exert powerful antioxidant [15,31], antiinflammatory [32] and anti-apoptotic effects [33][34][35], leading to reduced infarct size [16,17,[36][37]. However, emerging evidence, suggests that HO-1 may also exert cytoprotective effects, independent of heme breakdown [38] by interacting with survival signaling pathways such as PI3K-Akt and p38.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytoprotective properties of HO-1 have traditionally been attributed to the by-products of heme degradation, namely bilirubin and carbon monoxide (CO). Indeed, within a narrow therapeutic range, these catalytic by-products exert powerful antioxidant [15,31], antiinflammatory [32] and anti-apoptotic effects [33][34][35], leading to reduced infarct size [16,17,[36][37]. However, emerging evidence, suggests that HO-1 may also exert cytoprotective effects, independent of heme breakdown [38] by interacting with survival signaling pathways such as PI3K-Akt and p38.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism by which HO-1 may protect cells or tissues against oxidative injury is by generating bilirubin from catabolism of heme. Several studies have demonstrated that exogenous bilirubin can protect against hypoxia induced injury in cultured cells and in isolated perfused hearts subjected to I/R injury [15][16][17]. Furthermore, a strong correlation has been reported between elevated plasma bilirubin levels and lower risk of cardiovascular diseases [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, considerable evidence suggests an important role for HO-1 in cytoprotection. The induction of HO-1 by chemical inducers or selective overexpression of HO-1 provides cellular protection in cultured cells and in several animal models of brain, heart, kidney, lung, and liver failure (Abraham et al, 1995;Agarwal et al, 1995;Amersi et al, 1999;Otterbein et al, 1999;Panahain et al, 1999;Clark et al, 2000;Hangiashi et al, 2000;Yet et al, 2001;Coito et al, 2002). Studies with HO-1 À/À mice also support the functional significance of HO-1 in cytoprotection.…”
Section: Ho-1 and Cell Deathmentioning
confidence: 95%
“…However, differences in cell types and experimental conditions used can explain differences in results. For instance, we found that perfusion of isolated rat hearts with serum-free buffer containing bilirubin at concentrations as low as 100 nM reduces infarct size and improves myocardial function following ischaemia-reperfusion [16].…”
Section: Figure 4 Effect Of Exogenous Bilirubin On Gox-mediated Cell mentioning
confidence: 99%
“…In previous studies we have reported that exogenously applied bilirubin attenuates hydrogen peroxide-induced damage in vascular endothelial cells [14]. More recently, we have implicated HO-1-derived bilirubin in reduction of endothelial apoptosis mediated by peroxynitrite [15] and amelioration of postischaemic myocardial dysfunction in the isolated perfused rat heart [16]. Dore!…”
Section: Introductionmentioning
confidence: 98%